Multiple elements MIMO antenna system with broadband operation for 5th generation smart phones - Kiani, Saad Hassan; Iqbal, Amjad; Wong, Sai-Wai; Savcı, Hüseyin Şerif; Alibakhshikenari, Mohammad; Dalarsson, Mariana (IEEE-Institute of Electrical and Electronics Engineers Inc., 2022)
In this work, a simple, low-cost, dual wideband sub6GHz Multiple Input Multiple Output (MIMO) antenna system for a smart phone is presented. The antenna system is fabricated using inexpensive and commercially easily available 0.8 mm thick FR4 substrate. The presented system consists of a single main board and two side boards containing eight antennas and feedings. The radiating elements are etched on the side boards to provide space for other electronic components and RF systems and sub systems. The dimensions of the main board and the two side boards are 150 x 75 x 0.8 mm(3) and 150 x 6 x 0.8 mm(3), respectively. The radiating elements are etched on the side substrates and the feeding network is designed on the main board. The proposed system resonates at 3.5 GHz and 5 GHz providing -10 dB bandwidth of 250 MHz (ranges from 3.3 GHz to 3.55 GHz) and 1700 MHz (ranges from 4.2 GHz to 6.2 GHz), respectively. The design and the arrangement of the structure enable pattern diversity and ensures at least -15 dB of isolation between any two given radiating elements. Moreover, various different key performance parameters such as envelope correlation coefficient (ECC), mean effective gain (MEG), channel capacity (CC), specific absorption rate (SAR), gain, and efficiency are also presented. It is found that the peak gain of the system is 5.8 dBi, ECC is lower than 0.015, efficiency ranges between 58% to 78%, peak SAR is 1.28 W/Kg, and the maximum CC is 40.2 bps/Hz within the frequency band of interest. In addition, to further demonstrate the usefulness of such structure as a smart mobile terminal, single and dual hand scenarios are also presented. To validate the concept and the computed results, a prototype is fabricated and measured. It is found that the simulated results are in very good agreement with the measured results. Based on the performance and the measured results, we believe that this structure holds a promising future within the next generation smart mobile phones.
Keywords: Multi-Input-Multi-Output (MIMO); Wideband; Mutual Coupling; Envelope Correlation Coefficient (ECC); Pattern Diversity; Gain